Lack of association between LTF gene polymorphisms and different caries status in primary dentition - Wang, Mengchen; Qin, Man (Oral diseases, 2018)
Objective Dental caries is related to cariogenic bacteria, salivary components, oral hygiene and host susceptibility. Lactoferrin is an important antimicrobial glycoprotein in saliva; however, the role of the LTF gene in caries susceptibility is unclear. We investigated the association between LTF polymorphisms and the severity of caries. Design Our study included 910 healthy paediatric subjects (aged 24–48 months) categorised into three groups: 403 with no caries or white‐spot lesions; 230 with moderate caries (8 ≤ dmft ≤ 12); and 277 with severe caries (13 ≤ dmft ≤ 20). Information regarding the subjects’ oral habits was gathered using questionnaires. The LTF rs1126477 and rs1126478 polymorphism alleles were genotyped by Sanger sequencing. Results The three groups showed no significant differences in LTF polymorphisms alleles, genotypes or haplotypes distribution. Multifactor dimensionality reduction analysis showed that the interactions between breastfeeding for a duration >24 months, night feeding >24 months and high frequency of sweet food intake increased the risk of caries (p = 0.0014); however, we detected no interaction effect between the LTF polymorphisms and oral habits on caries susceptibility. Conclusions The LTF rs1126477 and rs1126478 polymorphisms showed no association with the different levels of caries risk in our Chinese paediatric cohort.